Religion in Philanthropic Organizations : Family, Friend, Foe? - Davis, Thomas J. (Thomas Jeffery), 1958- (Book collections on Project MUSE., 2013)
This book explores the tensions inherent in religious philanthropies across a variety of organizations and examines the effect assumptions about "professional" philanthropy have had on how religious philanthropies carry out their activities. Among the organizations discussed are the Salvation Army, the World Council of Churches, and Catholic Charities USA. The essays focus on the work of one individual, Robert Pierce, founder of World Vision and Samaritan's Purse, and on more general matters such as philanthropy and Jewish identity, American Muslim philanthropy since 9/11, and the federal program that funds faith-based initiatives. The book sheds light on how religion and philanthropy function in American society, shaping and being shaped by the culture and its notions of the "common good." -- Publisher's website.